The Idea of Life as the First Form of Truth and Freedom - Ebeturk, Emre (Studia Hegeliana, 2021)
In Hegel’s philosophy, both truth and genuine freedom belong to the domain of the Idea. Life, as it is categorized in the Science of Logic, is the first form and stage of the Idea, and is therefore essential for a comprehension of truth and self-determination. In this paper, I explore why and to what extent Life is self-determining and true. Considering what Hegel considers to be the three fundamental features of all life, I explain how life is self-determining with respect to its organic unity, relationship with the other, and reproductive process. I explicate how the living individual develops and sustains the collective unity of its objectivity, distinguishes itself from its other, yet sustains and regenerates itself through it, and how it raises its universal identity beyond its particular existence through reproduction.